2023
DOI: 10.1536/ihj.23-022
|View full text |Cite
|
Sign up to set email alerts
|

Normal Ventricular and Regional Blood Flow Volumes and Native T1 Values in Healthy Japanese Children Obtained from Comprehensive Cardiovascular Magnetic Resonance Imaging

Abstract: Age-related mean and reference ranges for ventricular volumes and mass, regional blood flow measurements, and T1 values using cardiovascular magnetic resonance (CMR) imaging are yet to be established for the pediatric population. Especially in infants and toddlers, no consistent flow volume sets or T1 values have been reported. The purpose of this study was to determine the relevant normal values.Twenty-three children (aged 0.1-15.3 years) without cardiovascular diseases were included. Comprehensive CMR imagin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
1
1
0
Order By: Relevance
“…Leah et al reported that the median LT1 in controls measured by 1.5-T MRI, was 569 ± 39 ms (range, 529-646; n = 12; mean age, 12.2 ± 3.1 years), similar to our control data. In this report, there was no signi cant association between age and LT1 [18], but this was not observed in our study, similar to our previous report [17]. Compared with these control data, the LT1 of the BVR and bidirectional Glenn circulation groups were almost the same as the control data, while the LT1 of the Fontan circulation group was higher in our study.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Leah et al reported that the median LT1 in controls measured by 1.5-T MRI, was 569 ± 39 ms (range, 529-646; n = 12; mean age, 12.2 ± 3.1 years), similar to our control data. In this report, there was no signi cant association between age and LT1 [18], but this was not observed in our study, similar to our previous report [17]. Compared with these control data, the LT1 of the BVR and bidirectional Glenn circulation groups were almost the same as the control data, while the LT1 of the Fontan circulation group was higher in our study.…”
Section: Discussionsupporting
confidence: 81%
“…Although no healthy control was included in this study, the mean LT1 of healthy controls measured by 1.5-T MRI at our institution was 552 ± 42 ms (n = 23, mean age: 7.2 ± 4.9 years) [17]. Leah et al reported that the median LT1 in controls measured by 1.5-T MRI, was 569 ± 39 ms (range, 529-646; n = 12; mean age, 12.2 ± 3.1 years), similar to our control data.…”
Section: Discussionmentioning
confidence: 99%